EFFECT OF CALCIUM AND VITAMIN D SUPPLEMENTATION IN PREGNANT WOMAN WITH HYPERTENSION AT SENTANI COMMUNITY HEALTH CENTER - Martina Mogan; Endang Trisnawati (POLTEKKES KEMENKES JAYAPURA, 2022)
Low calcium intake causes an increase in high blood pressure by stimulating the release of parathyroid hormone and renin, which causes an increase in intracellular calcium concentration in the smooth muscle cells of blood vessels and results in vasoconstriction. This study aims to determine the effect of giving calcium and vitamin D supplements to pregnant hypertension women on the anthropometric outcomes of newborns. The research design was quasi-experimental with two groups of post-test-only design. A respondent of 30 hypertension pregnant women at 28-32 weeks of gestation was selected by purposive sampling—data analysis using Mann Whitney. Calcium supplements (2 x 500 mg/day) and vitamin D3 (400 IU/day) were administered and monitored for eight weeks to 15 pregnant women as the intervention group and 15 pregnant women as the control group who were assumed to receive calcium supplements from the Health Service Program. Data on blood pressure and calcium levels were taken before and after eight weeks of intervention. The results showed that there was a significant difference in mean blood pressure between the control and intervention groups, with a p-value of systolic blood pressure (0.002) and a p-value of diastolic blood pressure (0.014), and the average decrease in blood pressure was more significant in the intervention group. There were differences in anthropometric results between the intervention group and the control group, with p-value s ​​for body weight (0.000), body length (0.000), and head circumference (0.000). The intervention group's average weight, length, and head girth were higher than the control group's. Thus, for eight weeks, calcium and vitamin D supplementation in hypertensive pregnant women can reduce blood pressure and result in better baby weight, body length, and head circumference. Keywords: Anthropometry, Calcium, Hypertension, Vitamin D